2018
DOI: 10.1016/j.addbeh.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Perceived academic benefit is associated with nonmedical prescription stimulant use among college students

Abstract: The results underscore the need for interventions that simultaneously correct misperceptions related to academic benefit and target alcohol and marijuana use to reduce NPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 45 publications
5
41
0
7
Order By: Relevance
“…Conversely, full-time students and college graduates had higher stimulant-PDM and stimulant SUD symptom rates. While young adults with higher levels of educational attainment have lower substance use rates (e.g., Grant et al, 2017), the elevated stimulant-PDM in full-time college students here and in Ford and Pomykacz (2016) may result from the predominant studying-related motives (Teter et al, 2006) and perceived academic benefits of stimulant-PDM (Arria et al, 2018). In these subgroups, elevated stimulant-PDM mirrored elevated rates of any stimulant use, with this positive relationship between any use and PDM seen broadly across subgroups and medication classes.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, full-time students and college graduates had higher stimulant-PDM and stimulant SUD symptom rates. While young adults with higher levels of educational attainment have lower substance use rates (e.g., Grant et al, 2017), the elevated stimulant-PDM in full-time college students here and in Ford and Pomykacz (2016) may result from the predominant studying-related motives (Teter et al, 2006) and perceived academic benefits of stimulant-PDM (Arria et al, 2018). In these subgroups, elevated stimulant-PDM mirrored elevated rates of any stimulant use, with this positive relationship between any use and PDM seen broadly across subgroups and medication classes.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high rates of stimulant misuse among university students have been attributed to various factors such as the desire for a “cognitive enhancer” to help with school work, to lose weight and look better physically, to improve alertness, the positive portrayal of stimulants on the Internet, and perception that stimulants assist in coping with psychological distress (Ford et al, 2014; Looby and Sant'Ana, 2018; Poulin, 2007; Schepis et al, 2008; Wilens et al, 2008; Weyandt et al, 2009). One study of college students found that 28.6% agreed or strongly agreed that the nonmedical use of prescription stimulants could help earn higher grades (Arria et al, 2018). For a review of the multi-faceted reasons for stimulant use on college campuses, see Bavarian et al, 2015…”
Section: Introductionmentioning
confidence: 99%
“…This concern takes on reality when we consider the previous finding that psychostimulants not only enhance cognitive performance, but also induce overconfidence in one's own performance [5]. A recent study indicated that approximately 65% of college students who use stimulants believe them to be effective in improving their academic performance [42]. However, the GPA of college students who had never used stimulants increased as the school year proceeded, whereas the grades of the students who started or continued to use stimulants did not improve [43].…”
Section: Continuity Between Pain Relief Pleasure Seeking and Enhancmentioning
confidence: 97%